(3TQM GdYjhfs - (3GdMHTi GdHjgbj GdHQhbfis; (3eMeO Hf EHQGgje Hf Ydj Hf GdeQJVj Hf GdeaVd GdMSfj GdbGSej, CHh YHO Gddg, YR GdOjf, ef Bd GdhRjQ,J (B840 (3g` s
(3ChdgG (B:s
(3GdbSe GdYGTQ GdcdGe ai GddWja eSdg GdeYOhe fUM Cf fYde YfOfG NdGakG dLgfe s
(3BNQgG (B:s
(3eSdI GdUaGJ Ydi VQhH efgG UaI GdPGJ hbGd GdbGVi hgh eG jLQi eLQi GdJNNUjU hGdJLfjS hGdCbQH hGdChVM eG bGdg TjNGfG s
(3cJHJ dNRGfI CHj GdMSjf jMji Hf ebHd GdedbH HMQhL cJH s
(3ai GdhQbI GdCNjQI HNW eZGjQ Cf GdfGbU ef gPG GdLRA hQbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B210s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds